Local Potential Integrated Science: New Innovation to Support Student’s Interest - Nisa, Wilda Muhimmatun; Tyas, Rizki Arumning (LPPM Institut Studi Islam Sunan Doe, 2023)
Utilizing local potential in learning can make students understand the object of material in daily life, its giving a positive impact on higher learning interests. This research aimed to find out student’s interest in learning science after using local potential integrated learning. The subject of the study was a class of students in one of Yogyakarta Junior High School 7th grade, consist of 30 students. This was Pre Experimental research with One Group Pretest Postest research design. The sample choosed by purposive sampling techniques. The instrument used was learning interest questionnaires. The poll was developed by researchers, by showing indicators of learning interest with 23 questions. The data analysis using paired sample t-test and n-gain test. The result shows that the significance value in paired sample t-test is 0.000, lower than 0.05, so it can be said that local potential integrated learnig is significance in increasing students' science learning interest. The average N-gain of student's learning interest increased before and after treatment by 0.60, belong to moderate criteria.